The evolving high bar longswing in elite gymnasts of three age groups - Burton, S.; Newell, K. M.; Exell, T.; Williams, G. K. R.; Irwin, G. (Journal of Sports Sciences, 2023)
Chronological age classifies elite male gymnasts into developmental performance classifications: senior (18+ years), junior (14-18 years) and development (8-14 years). Here, we examine the influence of age and experience on the biomechanics of the high bar longswing across classifications. Joint angular kinematics and kinetics were obtained from 30 gymnasts performing three sets each of eight consecutive longswings. Differences between groups and relations between age, experience and key biomechanical variables were correlated. Kinetic variables and range of motion of the hip and knee were highest for development gymnasts. In all age groups, a dominant shoulder kinetic contribution was found, although circle location of the peak joint kinetics occurred earliest for junior gymnasts. Hip work contributed more prominently in development gymnasts. Age and experience were positively correlated to an increase in peak shoulder moments and powers and negatively correlated to peak hip and knee moments. The findings reveal that age and experience combine to influence the functional phase, joint kinematics and relative joint kinetic contribution, particularly with the senior group demonstrating a shoulder dominant technique. Changes in musculoskeletal loading across the age groups suggest that factors such as relative strength and practice may have influenced this joint mode transition of the longswing.